Forecasting Model using Single Exponential Smoothing Method on PT. Rakha Medika - Hanna Christy; Andri Wijaya (Universitas Wahid Hasyim, 2026)
PT. Rakha Medika is a healthcare company with a network of clinics spread across various branches in the city of Palembang. In stock management, the company faces significant challenges related to both overstocking and stock shortages, which impact operational efficiency. These issues arise because inventory orders are made without proper planning. This study aims to optimize stock management by applying the Single Exponential Smoothing forecasting method to analyze usage patterns. The data used includes inventory records spanning a one-year period (April 2023 to April 2024), comprising a total of 4,033 entries. The forecasting results indicate that an alpha value of 0.99 is the most optimal, achieving a forecasting accuracy of MAPE at 14%, MAD at 4, and MSE at 97. These results suggest that the forecasting method performs reasonably well, as the MAPE score does not exceed 20%. However, a comparison between the forecasting results and the actual values reveals a deviation of 38.24% from the total inventory. This deviation is influenced by the characteristics of the data and unavoidable external factors.